DDA Algorithm for Path Planning - Dhanraj, Abhishek; Zope, Bhushan; Jafri, Syed Mujtaba; Buchade, Amar (2023 International Conference on Integration of Computational Intelligent System (ICICIS), 2023)
Technology is emerging day by day, and the world is getting automated. Hence, robots play a vital role in this world, from serving in restaurants to working in industries. Still, the common problem related to robots is finding the optimal shortest path to reach its destination. For finding the shortest path, the traditional A* algorithm is used. Still, in some situations, there are issues with the path found by the traditional method that is not optimally shortest or does not give results in minimum time. In this paper, an improvised DDA* algorithm is introduced, which is influenced by the shortest line segment that connects source and destination. The obstacles that appear on the shortest line segment are tackled by use of the A* algorithm. This DDA* algorithm performs better than the traditional A* algorithm in certain situations.